The Development Of The Administrative Apparatus In Kairouan Under The Ottoman Rule 1574-1881 AD (Damascus University Journal of Historical Studies, 2023)
This research aims to spot alight on the departments of the administrative apparatus, its positions and tasks in the city of Al-Kairouan, through the Ottoman rule and the new composition of the administrative system through the administrative positions of the leader of Kairouan and his deputy and tasks which represents the governor with military influence, and Al-Kahieh or the leader vice (deputy and tasks).And the judiciary and its role in the administrative arrangement, and the role of the Sheikhs and the councils.The research dealt with the areas of administrative expansion in the city Al-Kairouan, the military systems, and the administrative organization of military structures in the city such as The Corps Military plan, the private forces and the reserve forces which is known as (Zwazah Military)The research also includes a few documents (letters that owned by the Tunisian National Achieves) which reflects the prevailing administrative reality at the period.
Keywords: The Administrative Apparatus; Kairouan; The Ottoman Rule